The effects of Hedera helix on viral respiratory infections in humans: A rapid review. Issue 4 (December 2020) - Barnes, Larisa AJ; Leach, Matthew; Anheyer, Dennis; Brown, Danielle; Carè, Jenny; Lauche, Romy; Medina, Daen N; Pinder, Tobey-Ann; Bugarcic, Andrea; Steel, Amie
Abstract : Brief overview: Based on the evidence identified in this rapid review, Hedera helix preparations and herbal complex preparations including H. helix may be a therapeutic option for treating early symptoms of respiratory tract infections. The best effectiveness for H. helix preparations has been proven for coughing, as an expectorant and to reduce the frequency and intensity of cough. Only weak evidence was found for all other researched symptoms. Both adults and children tolerate H. helix well. Currently, there is insufficient evidence to recommend the use of this supplement in the treatment or prevention of COVID-19. However, the current evidence justifies further research to better understand its applicability in coronavirus infections. Verdic: tCurrent evidence suggests H. helix may improve the frequency and intensity of cough associated with viral respiratory infection. The overall applicability of additional findings is limited by the poorly defined outcome measures employed. However, studies focused explicitly on expectoration did report an increased conversion from dry to productive cough, and an improvement in expectoration amount, consistency and colour. These effects may be explained by a related finding of reduced oropharyngeal congestion and improved inflammatory markers (erythrocyte sedimentation rate and c-reactive protein). A decrease in frequency of night cough and respiratory pain was also reported, as was improved sleep quality and reduced cough-related sleep disturbance. Some studies also measured general respiratory tract infection symptoms and identified clinical improvement or resolution of fever, fatigue, sore throat, sneezing, wheezing, nasal congestion, post-nasal drip and body-ache. A reduced need for antibiotic prescriptions was also identified. While not consistently reported, the majority of studies also found H. helix reduced the overall severity of viral bronchitis and related conditions. Tolerability was rated as between 'good' and 'high'. Adverse events were rare or non-existent in almost all studies, and those that were reported were defined as non-serious and not drug-related.